Diabetic foot ulcer risk assessment and prevention in patients with diabetes: a best practice implementation project. Issue 4 (10th December 2022) - Yang, Lixiao; Wu, Yanni; Zhou, Chunlan; Xie, Cuihua; Jiang, Ya; Wang, Run; Ye, Xiaoling
ABSTRACT: Introduction and aim: Diabetic foot ulcer (DFU) is one of the most serious complications in patients with diabetes. Early identification of risk factors can prevent its occurrence and delay its progression. The aim of this project is to conduct an audit of DFU risk assessment protocols at a large tertiary hospital and evaluate the impact of any changes in compliance with the developed evidence-based best practice criteria. Methods: Preimplementation and postimplementation audits based on JBI's Practical Application of Clinical Evidence System were conducted at the Department of Endocrinology and Metabolism of a tertiary hospital in China. The Getting Research into Practice audit tool was used to analyze the barriers and inadequacies encountered in practice. A total of 12 nurses and 30 patients with diabetes were included in the baseline and follow-up audits. Results: There were 15 baseline audits that indicated deficits in DFU risk assessment by nurses, with 0% compliance for three criteria and 50% compliance or less for seven others. Strategies developed by the project team to address the identified barriers to compliance were adopted, leading to significant improvement in compliance with most criteria at the follow-up audit compared with baseline with 11 criteria achieving at least 90% compliance. Conclusion: The project showed that regular audits of foot ulcer risk assessment can help to identify barriers to their implementation. Advising patients of their risk status can support appropriate self-care practices. Further audits are needed to implement evidence-based practices in all aspects of diabetes patient care.